Learning Innovation through Artificial Intelligence to Improve Writing Skills of Islamic Religious Education Students - Daryono; Mahmudulhassan (Advances Educational Innovation, 2024)
Objective: This study aims to explore the role of artificial intelligence (AI) in enhancing the writing skills of Islamic Education (PAI) students through innovative learning approaches.Methods: Utilizing a qualitative research methodology, this study conducts a descriptive text analysis of literature relevant to AI and education. Data were gathered through library research, encompassing theses, dissertations, and scholarly articles, with a focus on 35 key sources identified via Google Scholar.Results: The findings indicate that AI significantly contributes to personalized learning by providing tailored feedback and facilitating access to instructional materials. AI systems enhance students' writing coherence, structure, and creativity while addressing technical aspects such as grammar and plagiarism detection.Novelty: This research offers new insights into the integration of AI in Islamic education, highlighting its potential to transform pedagogical approaches and foster collaborative learning environments among PAI students.Conclusion: The study underscores the necessity for educational institutions to adopt AI technologies to improve writing skills and develop dynamic, effective, and personalized learning experiences within the Islamic Education framework.